Pityriasis amiantacea : A reaction pattern of the scalp in psoriatic patient - Bhuiyan, Ishrat; Hossain, Md Shahadat; Rahman, Md Moksedur; Joarder, Yasmeen (Northern International Medical College Journal, 2016)
Abstract not available Northern International Medical College Journal Vol.7(2) Jan 2016: 156-157